The The Effect of Financial Performance, Profitability, and Company Growth on Company Value in the Mining Company Sector in â€œBeiâ€ 2021-2023 Period: Pengaruh Kinerja Keuangan, Profitabilitas Pertumbuhan Perusahaan terhadap Nilai Perusahaan pada Sektor Perusahaan Pertambangan di BEI Periode 2021-2023 - Wamea, Joddy Vina Geralldine; Artaningrum, Rai Gina; Wasita, Putu Aristya Adi (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2025)
Company value maximization is crucial because it maximizes shareholder prosperity, the company's main goal. The increase in company value can also attract investors to invest their capital. Several factors that affect the value of the company are its financial performance. This study aims to obtain empirical evidence regarding the effect of financial performance and profitability on company growth and company value in the mining company sector in â€œBeiâ€ for the period 2021â€“2023. This research was conducted at companies belonging to the mining sector on the Indonesia Stock Exchange in 2021-2023. The sampling method used is purposive sampling, with valid data for 20 companies with the criteria that companies publish consecutive annual reports during the 2021â€“2023 period to obtain 60 observations. Regression data analysis techniques and data were processed using SPSS version 25. Based on the results of the study, it is known that financial performance proxied by capital structure has a positive and significant effect on firm value, profitability has a positive and significant effect on firm value, and company growth has a positive and significant effect on firm value.